Fluoride removal from water by chitosan derivatives and composites: a review - Miretzky, Patricia (2011)
Fluoride is an essential element, indispensable for maintenance of dental health. Nevertheless, fluoride concentrations in drinking water above 1.5 mg L−1 may be detrimental to human health. Many methods have been developed for removing excessive fluoride from drinking water, adsorption seems to be an effective, environmentally friendly and economical one. Since the sorption capacity of fluoride below 2 mg L−1 on most conventional adsorbents is not satisfactory, much effort has been devoted to develop new and cost-effective fluoride adsorbents. This review reports the recent developments in the F− removal in water treatment, using chitosan derivatives and composites in order to provide useful information about the different technologies. When possibly the adsorption capacity of chitosan derivatives and composites under different experimental conditions is reported to help to compare the efficacy of the fluoride removal process. A comparison with the adsorption capacity of other low cost adsorbents is also tabled.